MODERASI MONEY ATTITUDE DAN MEDIA EXPOSURE DALAM MODEL GAMBLING BEHAVIOR PADA MAHASISWA AKUNTANSI - Ghoin Ashar Syakara; Budi Barata Kusuma Utami (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study examines the effect of gambling motives on gambling behaviour with money attitude and media exposure as moderating variables in accounting students. The sample of this study amounted to 101 accounting students who were randomly selected. The analysis technique used is SEM PLS with the help of the SmartPLS3.0 application. The results of this study indicate that gambling motives have a significant influence on gambling behaviour, but money attitude and media exposure do not moderate this influence. This study contributes to the literature on gambling behaviour and can be a consideration for the world of education to educate students regarding the risks of gambling. The current study targeted interventions and educational programs are required for gambling behavior among university students, in particular, those studying finance-related subjects. Therefore, these findings can be useful in the design of curriculum elements which have the aim of raising the awareness of students about the risks of gambling and financially responsible behaviors.